SEASONAL AND SUBSEASONAL CLIMATE CHANGES RECORDED IN LAMINATED DIATOM OOZE SEDIMENTS, ADÉLIE LAND, EAST ANTARCTICA - Denis D.; Crosta X.; Zaragosi S.; Martin B.; Mas V.; Romero O. (My University, 2006)
A 40 m long sediment core covering the 1000-9600 years BP period was retrieved from the Dumont d'Urville Trough off Adelie Land, East Antarctica, during the MD 130-Images X-CADO cruise. This sedimentary sequence allows the documentation of changes in climate seasonality during the Holocene. Here we show preliminary results of diatom communities, lithic grain distribution and titanium content measured on two 30 cm long sequences of thin sections. The two sequences originate from two different climate regimes, the colder Neoglacial and the warmer Hypsithermal. Proxies were measured at microscale resolution on 25 laminations for the Neoglacial and 14 laminations for the Hypsithermal. The two sequences reveal alternating light-green and dark-green laminae. Light laminae result from low terrigenous input and high sea-ice edge diatom fluxes and are interpreted to represent the spring season. Dark laminae result from high terrigenous input mixed with a diversified open ocean diatom flora and are interpreted to represent the summer-autumn season. The two sequences therefore resolve annual couplets composed of one light plus one dark lamina. Variations in the relative thickness of laminations and annual couplets, associated with diatom assemblage changes, are observed in each sequence and between the two sequences giving information on interannual to millennial changes in environmental conditions. © 2006 SAGE Publications.
Keywords: ADÉLIE LAND; DIATOM OOZE; EAST ANTARCTICA; HOLOCENE; LAMINATED SEDIMENTS; SEA ICE; SEASONALITY; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен